Perception and Attitudes Toward PPE-Related Waste Disposal Amid COVID-19 in Bangladesh: An Exploratory Study - Islam, S. M. Didar-Ul; Safiq, Mariam Binte; Bodrud-Doza, Md.; Mamun, Mohammed A. (Frontiers in Public Health, 2020)
Personal protective equipment (PPE) is an essential item to protect from exposure to infectious pathogens or contaminants, which is frequently used at health care settings and public spheres since the coronavirus disease 2019 (COVID-19) outbreak. There is no prior study investigating public perception and attitudes toward PPE-related waste disposal in Bangladesh. Hence, an online survey was carried out among 1,303 Bangladeshi adult residents to explore the issue. Results stated that face mask and hand gloves were the widely used PPE, where around 45.50% mask and 31.60% hand gloves were disposable. Approximately 94.50% of the participants percepted to use at least one type of PPE while going outside. Only 18.65% of the respondents percepted to burn the PPE-related waste, while most of them reported other less protective disposal measures. Females, urban residents, and participants with higher education were found to have better perception and attitudes toward PPE-related waste disposal. To the best of the authors' knowledge, being the first exploratory study in the country, the present findings are anticipated to be helpful at policy levels with respect to arranging awareness programs.